Survey on the Role of Employers and the Scope of Existing Retention Policies in Startup Ventures - Sharma, Shiwangi; Srivastava, Nandini (International Journal of Psychosocial Rehabilitation, 2020)
The concept of startups is in a glowing stage within the national boundary, but as per the declaration of George Bernard Shaw, “The first condition to progress is the removal of censorship,” hence a critical study to understand and find the elucidation of the real challenge of startups, i.e., employee retention, is taken into thought. After going through various concerned literature, it was found that employee retention in startup ventures and the role of employers in the same on a pan-India basis is a rare study within research. Hence, an exploratory study has been done to reconnoiter the concept. Primary research by the help of a survey-based mixed questionnaire was done on the sample size of 100 respondents. The collected data was analyzed quantitatively from SPSS by descriptive statistics and cross tabulation of the two independent variables, i.e., gender and place. The analysis shows various counts of dependent variables in relation to those of independent variables in the form of percentages. Qualitative analysis too comes from some subjective and open-ended questions, which are noted in the form of narratives. Moreover, the interpretation and conclusion redirect that employers are implementing various retention policies to increase their employee retention rate, but as there is always a scope of development, respondents have marked less on the grounds of flexibility in the workplace, fun activities, and friendly work culture and thus have suggested the same for implementation.